EXTRACELLULAR BIOSYNTHESIS OF SILVER NANOPARTICLES USING ASPERGILLUS FLAVUS AND THEIR ANTIMICROBIAL ACTIVITY AGAINST GRAM NEGATIVE MDR STRAINS - SHIVARAJ NINGANAGOUDA; VANDANA RATHOD; JYOTI.H; DATTU SINGH; PREMA.K; MANZOOR-UL-HAQ (International Journal of Pharma and Bio Sciences, 2013)
To develop a reliable, ecofriendly procedure for bioreduction of silver nanoparticles by Aspergillus flavus. Methods: Characterization was done by using UV-VIS spectrophotometry, Infrared spectroscopy (FT-IR) and X-ray diffraction. Results: IR spectroscopy showed the potential biomolecule responsible for the reduction of silver nanoparticles and stability of the bioreduced silver nanoparticles. X-ray diffraction analysis showed that the particles were crystalline in nature with face centered cubic geometry. Conclusion: A.flavus was found to be a good producer of silver nanoparticles by releasing the extracellular enzyme nitrate reductase. Silver nanoparticles are known to have inhibitory and bactericidal effects against MDR strains of Pseudomonas aeruginosa, Escherichia coli and Klebsiella pneumonia. Resistance of bacterial infections has emerged in recent years and is a major health problem. Here, we report the extra cellular biosynthesis of silver nanoparticles using the fungus, Aspergillus flavus and its antibacterial activities against pathogenic MDR strains.